2019
DOI: 10.1038/s41598-019-50276-z
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin enhances anticancer drug-induced toxicity mediated by the reduction of claudin-1 and 11 expression in a spheroid culture model of lung squamous cell carcinoma cells

Abstract: The aberrant expression of claudins (CLDNs), which are tight junctional proteins, is seen in various solid tumors, but the regulatory mechanisms and their pathophysiological role are not well understood. Both CLDN1 and CLDN11 were highly expressed in human lung squamous cell carcinoma (SCC). Chrysin, found in high concentration in honey and propolis, decreased CLDN1 and CLDN11 expression in RERF-LC-AI cells derived from human lung SCC. The phosphorylation level of Akt was decreased by chrysin, but those of ERK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Inhibition of CYP1B1 may interplay with these pathways leading to the chemo-sensitizing effects. [194] Isorhamnetin 17 [219] Protection from chronic DOX-induced cardiotoxicity in vivo in rats and in vitro in H9c2 cells [201] Potentiates DOX-induced toxicity in MCF-7, HepG2, and Hep2 cancer cells [201] Chrysin 24-270 [219,220] Protection from acute and chronic DOX-induced cardiotoxicity in vivo in rats [222,223] Enhanced cytotoxicity of DOX in a spheroid culture model of human lung squamous cell carcinoma [224], BEL-7402/ADM [225], lung cancer A549 cells [192], and human non-small-cell lung cancer cell lines [193] Apigenin 25 [219] Attenuated chronic DOX-induced cardiotoxicity in in vivo in rats and in vitro in rat cardiomyocytes [186][187][188] Augmented the cytotoxic effect of DOX against HepG2 cells [203], and DOX-resistant hepatocellular carcinoma cell line BEL-7402/ADM [204,218,226] Reverse chemo-resistance to DOX in DOX-resistant breast cancer cells (MCF-7/ADR) [198] Kaempferol 47 [219] Protected from chronic DOX-induced cardiotoxicity in vivo in rats and in vitro in H9c2 cells [227] Potentiated the cytotoxic effect of DOX in glioblastoma cells [205] Quercetin 77 [219] Protected rat and human cardiomyocytes and H9c2 cells from DOX-induced toxicity in vitro [176,188,189,199,228]. Protected from chronic DOX in rats [190,229] and mice [185] in vivo.…”
Section: Chemosensitizing Effects Of Cyp1b1 Inhibitorsmentioning
confidence: 99%
“…Inhibition of CYP1B1 may interplay with these pathways leading to the chemo-sensitizing effects. [194] Isorhamnetin 17 [219] Protection from chronic DOX-induced cardiotoxicity in vivo in rats and in vitro in H9c2 cells [201] Potentiates DOX-induced toxicity in MCF-7, HepG2, and Hep2 cancer cells [201] Chrysin 24-270 [219,220] Protection from acute and chronic DOX-induced cardiotoxicity in vivo in rats [222,223] Enhanced cytotoxicity of DOX in a spheroid culture model of human lung squamous cell carcinoma [224], BEL-7402/ADM [225], lung cancer A549 cells [192], and human non-small-cell lung cancer cell lines [193] Apigenin 25 [219] Attenuated chronic DOX-induced cardiotoxicity in in vivo in rats and in vitro in rat cardiomyocytes [186][187][188] Augmented the cytotoxic effect of DOX against HepG2 cells [203], and DOX-resistant hepatocellular carcinoma cell line BEL-7402/ADM [204,218,226] Reverse chemo-resistance to DOX in DOX-resistant breast cancer cells (MCF-7/ADR) [198] Kaempferol 47 [219] Protected from chronic DOX-induced cardiotoxicity in vivo in rats and in vitro in H9c2 cells [227] Potentiated the cytotoxic effect of DOX in glioblastoma cells [205] Quercetin 77 [219] Protected rat and human cardiomyocytes and H9c2 cells from DOX-induced toxicity in vitro [176,188,189,199,228]. Protected from chronic DOX in rats [190,229] and mice [185] in vivo.…”
Section: Chemosensitizing Effects Of Cyp1b1 Inhibitorsmentioning
confidence: 99%
“…The IC 50 dose of chrysin on prostate carcinoma cells was determined to be 24.5 ± 0.1 µM after 48 h of treatment. The neoplastic potential of chrysin is very well known 8 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inducing intrinsic and extrinsic apoptosis. Maruhashi et al 14 reported that chrysin enhances the anticancer potential of drugs in lung squamous cell carcinoma, suggesting its use as an adjuvant in chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Chrysin decreased CLDN1 and CLDN11 expression in human lung SCC (RERF-LC-AI) cells. Chrysin alleviated p-Akt and inhibited PDK1 and Akt [ 170 ]. NiCl2 (Ni) induced migration and invasion in A549 and H1975 human lung cancer cells.…”
Section: Cellular and Molecular Mechanisms Involved In The Therapeutic Effects Of Chrysinmentioning
confidence: 99%